Physician assistant dual employment. Issue 7 (July 2017) - Jeffery, Colette; Morton-Rias, Dawn; Rittle, Mary; Cannon, James; Hooker, Roderick S.
Abstract : ABSTRACT: National health workforce supply and demand models help predict requirements built on individual annual productivity assumptions. Dual employment rarely is addressed, yet in 2015, about 13.5% of certified physician assistants (PAs) reported two or more clinical positions. Of PAs working two positions, 44% reported the main reason was to supplement earnings, followed by role variety. The mean number of hours worked by all certified PAs was 40.7 per week and the average number of patients was 75. Dual-employed PAs averaged more than 51 hours and 97 patients per week. This new finding reveals an added dimension to provider productivity statistics requiring refinements to annual output calculations.